얕은 연못에서 담수 어류의 열성 스트레스 저감을 위한 피난처 개발 및 수질환경 조사 연구 - 이새로미(Saeromi Lee); 안창혁(Chang Hyuk Ahn); 주진철(Jin Chul Joo); 송호면(Ho Myeon Song); 박재로(Jae Roh Park) (Daehan hwan'gyeong gonghag hoeji, 2014)
The purpose of this study evaluates the water quality of artificial deep pool (ADP) during the late spring and summer. we monitored the water quality, as pH, dissolved oxygen (DO), temperature and conductivity at two stations (St. 1. open water, St. 2. in the ADP). The water quality in the ADP is very stable, and temperature and DO are lower than the open water (average value; temperature $1.4{\sim}3.2^{°}C$, DO 2.4~3.6 mg/L). In particular, daily variation of temperature in the open water showed above $4^{°}C$, but ADP remained stable. The water quality was analyzed using two-way analysis of variance (ANOVA). The results of the analysis showed difference about temperature, pH, DO, conductivity (two-way ANOVA, p<0.05). The ADP has created an aqua environment in thermal and DO gradients by depth. About 1.2 m, Temperature and DO were sharply decreased. The Rhodeus uyekii is dominant species in pond of this study. The ADP offers optimum water temperature ($16.5{\sim}18.5^{°}C$) to the Rhodeus uyekii about spawning. Consequently, the ADP offers stable habitat than open water for fish and aquatic organisms during the summer. It is also a good shelter for fish from a thermal stress. 본 연구는 얕은 연못에 시공된 지하 매립형 어류 피난처 구조물인 artificial deep pool (ADP)을 대상으로 늦봄~여름기간 동안 수질환경을 평가하고 그 특징을 파악하고자 하였다. 개방수역인 St. 1과 ADP인 St. 2로 구분하여 분석한 결과, St. 2는 St. 1보다 평균적으로 수온 $1.4{\sim}3.2^{°}C$, DO 2.4~3.6 mg/L 낮았고 일수질변동(daily water quality fluctuation)이 적은 안정된 공간으로 나타났다. 특히 수온의 일변화(daily variations)는 St. 1에서 ${≥}4^{°}C$을 보였으나, St. 2에서는 거의 변화가 없었기 때문에 고수온이 지속될 때 어류가 피난 공간으로 활용할 수 있음을 시사하였다. 이화학적 수질은 St. 1과 St. 2에서 큰 차이가 없었지만, 수온, pH, DO, 전기전도도에 대해서는 서로 뚜렷하게 다른 공간임을 나타내었다(two-way ANOVA, P<0.05). ADP 내부는 수심별로 thermal and DO gradient가 나타났으며, 수심 약 1.2 m 이후부터 급격히 감소하였다. 이러한 수질환경은 얕은 연못에서 어류의 서식 및 산란에 영향을 미치며, 본 연구의 조사지점의 연못에서는 각시붕어(Rhodeus uyekii)가 우점하는 것으로 보아, ADP가 적용되면서 납자루아과인 각시붕어의 적정 산란수온($16.5{\sim}18.5^{°}C$)을 제공하여 각시붕어가 서식하기 좋은 환경을 조성한 것으로 판단된다. 또한, ADP는 여름철에 수온이 높고, 변동이 큰 외부환경보다 낮은 수온을 일정하게 유지하여 수온변동 및 고온에 민감한 어종에게 좋은 피난처로 활용될 것으로 여겨진다.